2021
DOI: 10.1002/cta.3177
|View full text |Cite
|
Sign up to set email alerts
|

High‐voltage gain magnetically coupled half‐bridge Z‐source inverter

Abstract: In this paper, a new impedance-source inverter based on the half-bridge configuration is presented. The proposed topology has two switches that make four working modes. These operational modes are analyzed in detail, leading to obtaining the proposed topology's boost-factor. Besides, some equations are derived that are used to design passive elements such as capacitors and inductors. Besides, the voltage stresses on the switches and diodes are obtained. A comparative study from the boost-factor point of view i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 28 publications
(54 reference statements)
1
15
0
Order By: Relevance
“…Although a high boost factor can be obtained by increasing the number of these cells, the count of the passive components gets high dramatically. Aalami et al 33,34 present another topologies similar to the presented one in Aalami et al 34 Other three similar topologies can be found in previous studies. [35][36][37] In these structures, the components count is relatively low, and they can give a high boost factor regarding the use of transformers.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…Although a high boost factor can be obtained by increasing the number of these cells, the count of the passive components gets high dramatically. Aalami et al 33,34 present another topologies similar to the presented one in Aalami et al 34 Other three similar topologies can be found in previous studies. [35][36][37] In these structures, the components count is relatively low, and they can give a high boost factor regarding the use of transformers.…”
Section: Introductionsupporting
confidence: 78%
“…In this part, the proposed topology is contrasted with the current topologies in previous studies, 16–37 and the results are discussed. It is clear from (57) that the maximum output voltage of the proposed topology is determined by the sum of the magnitudes of the two voltage sources used.…”
Section: Comparative Studymentioning
confidence: 99%
See 3 more Smart Citations